Clinical Features of Congenital Cystic Lung Diseases: A Report on a Nationwide Multicenter Study in Japan - Kuroda, Tatsuo; Nishijima, Eiji; Maeda, Kosaku; Fuchimoto, Yasushi; Hirobe, Seiichi; Tazuke, Yuko; Nozawa, Kumiko; Matsuoka, Kentaro; Usui, Noriaki (European Journal of Pediatric Surgery, 2016)
Aim The current study aimed to assess the perinatal risk of congenital cystic lung diseases (CCLD) and to establish a suitable surgical strategy in consideration of postoperative lung growth and problems during adulthood.Methods Among 874 CCLD patients identified in a nationwide survey, 428 patients were born between 1992 and 2012 and treated at 10 high-volume centers were retrospectively reviewed with statistical analysis.Results In the 194 patients who were prenatally diagnosed to have CCLD, 16.7% presented with fetal hydrops as observed using ultrasonography. The Apgar score (5 minutes) was lower than 5 in 5.4%. As of postnatal day 30, 14.0% of the neonatal patients required respiratory support, and 3.3% (8/243) had died because of pulmonary hypoplasia. Among those who were asymptomatic immediately after birth, 33.6% of the patients developed the respiratory infectious symptoms during their first year of life, and 22.1% did so between the age of 1 and 2 years. The postoperative percent vital capacity among the prenatally diagnosed patients was significantly higher than that among the postnatally diagnosed patients (98.3 ± 11.9 vs. 81.7 ± 9.7, p < 0.0222). Late complications included thoracic deformity in 30 patients and persistent lung cyst in 4 patients, whereas malignancy was not observed in the present series.Conclusions Approximately 10 to 15% of prenatally diagnosed CCLD patients may carry a high risk of perinatal respiratory distress. Early operation before developing episodes of lung infection, seem to be associated with a better development of the reserved lung during later life. The incidence of carcinogenesis among patients with CCLD may be extremely low.
Keywords: congenital cystic lung disease; congenital cystic adenomatoid malformation; prenatal diagnosis; lung development